SAT0631 Inter-observer and intra-observer reliability of the omeract ultrasonographic (US) criteria for the diagnosis of calcium pyrophosphate deposition disease (CPPD) at the metacarpal-phalangeal (MCP), wrist, acromion-clavicular (AC) and hip joints. (15th June 2017) - Filippou, G; Scirè, CA; Damjanov, N; Adinolfi, A; Bruyn, G; Carrara, G; Cazenave, T; D'Agostino, M-A; Sedie, A Delle; Cortes, ME Diaz; Filippucci, E; Gandjbakhch, F; et al.
Abstract : Background: The OMERACT US subtask force "US in CPPD" recently created the definitions for US identification of crystal deposits in joints and tested the reliability at the knee [1]. Objectives: To assess the inter/intra-observer reliability of US on detecting CPPD at triangular fibrocartilage complex (TFCC) of the wrists, fibrocartilage of the AC joint, hip labrum (HL), hyaline cartilage (HC) of the metacarpal (MC) and femoral head. Methods: The OMERACT criteria for CPPD were used for the exercise [1] using a 2 steps approach. First, the panel of experts gave a dichotomous score (presence/absence of CPPD) of 120 images of the sites included, using a web platform. The images were evaluated twice to assess the inter/intra-observer reliability. Then, the experts met in Siena for a patient based exercise. Bilateral evaluation of TFCC, AC, HL /HC of the hip and HC of the II-III MCP of 8 patients was carried out twice in a day, using a dichotomous score for CPPD. 8 US machines (3 GE, 1 Samsung and 4 Esaote) equipped with high resolution linear probes were used. Results: Reliability values of static exercise were high for all sites, demonstrating that definitions were clear. The results of the second step are presented in table 1 . On live scanning, the TFCC resulted the most reliable site for CPPD assessment, followed by AC. Other sites demonstrated lower kappa values and thus are not reliable for CPPD assessment. Conclusions: TFCC of the wrist is the most reliable site for CPPD. By adding these results to the previous [2], we confirm that the OMERACT definitions for CPPD can be applied reliably at the knee (meniscus and HC), TFCC and AC, usually the most involved sites in CPPD. The next step of the OMERACT subtask force will be to test these findings in a longitudinal observational study. References: Filippou G, Scirè CA, Damjanov N et al. Definition and reliability assessment of elementary US findings in CPPD. Results of an international multi-observer study by the OMERACT sub-task force "US in CPPD". J Rheumatol, in press. Disclosure of Interest: None declared